Figurative Language in Sticks and Stones Standup Comedy by Dave Chappelle - Fauzy, Diki Rizky; Juanda, Juanda; Yuwita, Mia Rahmawati (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
This research analyzes the use of figurative language in Dave Chappelle's standup comedy special "Sticks & Stones." The issue addressed is how Chappelle employs various forms of figurative. The aim of this study is to identify and evaluate the types of figurative language used and understand how these techniques affect the messages conveyed and the audience's response. The research method used is qualitative text analysis, where transcripts of the comedy special are analyzed to identify metaphors, similes, irony, hyperbole, personification, metonymy. Data were collected through direct observation of the performance and related literature analysis to support the findings. The findings of the study show that Chappelle consistently uses figurative language, as well as to add deeper layers of humor to his material. Metaphors and irony emerge as the main tools used to highlight absurdities and injustices in issues such as cancel culture, identity politics, and freedom of speech. These results indicate that figurative language not only functions as a rhetorical tool but also as a mechanism to invite the audience to think critically about the issues raised. This research contributes to the development of knowledge by adding insights into the role of figurative language in standup comedy. It also expands the understanding of how comedians like Chappelle can use language techniques to influence public perception and encourage social dialogue. Keywords: Figurative language, Stand-up comedy, Dave Chappelle